2015
DOI: 10.1136/bcr-2015-213452
|View full text |Cite
|
Sign up to set email alerts
|

A neonate born withMycobacterium cosmeticumbacteraemia

Abstract: SUMMARYMycobacterium cosmeticum is a rapidly growing mycobacterium that was recently identified. However, its role in human infection has not been well described. We present a case of an extremely premature neonate born with bacteraemia due to M. cosmeticum that resolved without sequelae. The infection likely occurred during a prolonged intrauterine transfusion procedure. BACKGROUND

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“… 4 The first batch of bacterial strain was from drains and sinks at a nail salon in Atlanta, Georgia, USA, and a subcutaneous granuloma in a woman in Venezuela undergoing mesotherapy. Subsequently, there were more cases of M. cosmeticum infections reported, 8 , 9 , 10 , 11 , 12 , 13 , 14 including infections in the lung, joint, catheters, ascites, skin, and colon, as well as systemic infection. M. cosmeticum was also detected in the environment.…”
Section: Discussionmentioning
confidence: 99%
“… 4 The first batch of bacterial strain was from drains and sinks at a nail salon in Atlanta, Georgia, USA, and a subcutaneous granuloma in a woman in Venezuela undergoing mesotherapy. Subsequently, there were more cases of M. cosmeticum infections reported, 8 , 9 , 10 , 11 , 12 , 13 , 14 including infections in the lung, joint, catheters, ascites, skin, and colon, as well as systemic infection. M. cosmeticum was also detected in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the current literature revealed 12 reported cases of human clinical infections with M. cosmeticum [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] and 14 reported cases with M. canariasense [21] , [22] , [23] ( Table 1 ). M. canariasense is almost exclusively an opportunistic pathogen in severely immune compromised, while M. cosmeticum also infects normal hosts.…”
Section: Discussionmentioning
confidence: 99%
“…M. cosmeticum has been described to cause other infections as catheter-related bloodstream infection, 13 granulomatous colitis, 14 ascites, 15 16 and was described to cause bacteremia in a preterm patient. 17 …”
Section: Discussionmentioning
confidence: 99%
“…11 12 M. cosmeticum has been described to cause other infections as catheter-related bloodstream infection, 13 granulomatous colitis, 14 ascites, 15 16 and was described to cause bacteremia in a preterm patient. 17 The role of M. cosmeticum as a respiratory pathogen is not well established. It was isolated first from the sputum of an HIV patient in addition to Mycobacterium scrofulaceum.…”
Section: Case Reportmentioning
confidence: 99%